2020
DOI: 10.4149/gpb_2019056
|View full text |Cite
|
Sign up to set email alerts
|

Solubilisation of model membrane by DDAO surfactant – partitioning, permeabilisation and liposome-micelle transition

Abstract: Dedicated to prof. P. Balgavý on the occasion of his 75th birthday.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…The parameters of the model are scale factor Γ m , bilayer thickness d L (discussed in the next paragraph), number of layers N L , and repeat distance d (SANS analysis, eqs S5–S7). Our previous studies confirmed the suitability of the paracrystal lamellar model for lipidadditive oligolamellar vesicles (OLV). , …”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…The parameters of the model are scale factor Γ m , bilayer thickness d L (discussed in the next paragraph), number of layers N L , and repeat distance d (SANS analysis, eqs S5–S7). Our previous studies confirmed the suitability of the paracrystal lamellar model for lipidadditive oligolamellar vesicles (OLV). , …”
Section: Resultssupporting
confidence: 84%
“…These values correspond to the bilayer thickness reported d L = 3.76 nm of bovine lung surfactant in fluid state, and d L = 4.13 ± 0.02 nm derived for Curosurf at 40 °C by Oseliero Filho et al For protein-free MS, d L = 3.65 ± 0.02 nm was obtained from the best fit of the SANS data at 37 °C using the same model (Figure S11). The model was previously tested and, for comparison, we have obtained d L = 3.61–3.87 (±0.02) nm for ULV from DPPC and DOPC in the fluid state, while d L = 4.20 ± 0.02 nm for DPPC vesicles in the gel state. , …”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations